2006
DOI: 10.1002/app.22125
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of natural rubber in the presence of OsHCL(CO)(O2)(PCY3)2: Kinetics and mechanism

Abstract: ABSTRACT:The homogeneous catalyst precursor, OsHCl-(CO)(O 2 )(PCy 3 ) 2 , was utilized for the hydrogenation of natural rubber to convert the unsaturated structure to a saturated form, providing an alternating ethylene-propylene copolymer. A detailed kinetic investigation was carried out by monitoring the amount of hydrogen consumption during the reaction using a gas-uptake apparatus.1 H NMR spectroscopy was used to determine the final olefin conversion to the hydrogenated product. Kinetic data, collected acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Thus, the two glass transition temperatures observed for HSNR confirmed the layer model morphology for the hydrogenation as discussed in the previous section regarding the TEM study. Compared with the complete HNR produced from hydrogenation in the presence of OsHCl(CO)(O 2 )(PCy 3 ) 2 , all DSC thermograms of 99% HNR samples indicated the one step base-line shift at À61.8 C [17] and À59.6 C [18]. This implies that the HNR prepared from catalytic hydrogenation has a single glass transition temperature.…”
Section: Thermal Analysis Of Snrl Diimide Hydrogenationmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, the two glass transition temperatures observed for HSNR confirmed the layer model morphology for the hydrogenation as discussed in the previous section regarding the TEM study. Compared with the complete HNR produced from hydrogenation in the presence of OsHCl(CO)(O 2 )(PCy 3 ) 2 , all DSC thermograms of 99% HNR samples indicated the one step base-line shift at À61.8 C [17] and À59.6 C [18]. This implies that the HNR prepared from catalytic hydrogenation has a single glass transition temperature.…”
Section: Thermal Analysis Of Snrl Diimide Hydrogenationmentioning
confidence: 86%
“…[15][16][17][18][19], the extent of hydrogenation increased with increasing rubber concentration up to 0.55 M and then decreased. At high rubber concentration, the diimide species may self-decompose during the hydrogenation process resulting in a low degree of hydrogenation.…”
Section: Effect Of Process Parameters On Diimide Reductionmentioning
confidence: 99%
“…The C]C of the rubber are sensitive to oxygen, ozone and heat resulting in rubber degradation and the reduction of mechanical and thermal properties. Hydrogenation of diene-based rubbers is an important process to obtain hydrogenated rubber and improve their thermal properties and oxidative stability while maintaining their elastomeric properties [12]. NR latex was hydrogenated by diimide reduction, using hydrazine and hydrogen peroxide with copper sulfate as catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…11,15 A specific amount of NR (ca. 612.7 mM) dissolved in 1,200 mL of toluene with a small amount of 3-CPA (5 mM) was hydrogenated in a 2-L Parr reactor.…”
Section: Hydrogenation Of Nrmentioning
confidence: 99%
“…[9][10][11][12] It has been shown that the structure of NR is changed from cis-1,4-polyisoprene to an alternating ethylene-propylene copolymer upon hydrogenation, which has higher thermal stability without affecting the inherent glass transition temperature of NR. [11][12][13] Although the kinetics of NR hydrogenation and thermal properties of hydrogenated NR (HNR) have been investigated, there are few literature reports on the measurement of any technological properties of HNR vulcanizates and rubber blends containing HNR. Inoue and Nishio 14 studied NR hydrogenation catalyzed by RhCl(PPh 3 ) 3 at 70-80 C and 100% hydrogenation was achieved within 96 h. For their HNR materials, the mechanical properties of the HNR vulcanizates after aging were higher than NR and EPDM vulcanizates.…”
Section: Introductionmentioning
confidence: 99%